Značilnosti gnezdišč mestne lastovke Delichon urbica v Kozjanskem parku - Denac, Katarina (Acrocephalus, 2000)
During the course of the youth research camp at Kozjanski Park (June 25th July2nd 1999) a research about the breeding ecology of House Martin Delichon urbica in urban and rural habitats was carried out. 826 nests located on 69 buildings in 10 towns were counted. 31% of the nests were occupied by House Martins, 68% were empty. For the remaining 1 % of the nests no information on occupancy could be obtained. The number of occupied nests was probably underestimated since some House Martins had already reared their first clutch.Some of the abandoned nests were occupied by House Sparrows Passer domesticus and three by Spanish Sparrow Passer hispaniolensis male. Nests werelocated mainly on one- and two-storied houses, but all larger colonies (more than 20 nests) were located on higher and bigger houses. Less than 5% ofall the nests were located on shelves or supports. It seems very likely thatshelter from above (roof), suitable wall material and openness in front ofthe wall are more important than the shelf itself. The mean height of the nests was 7.4 m (median 7 m), ranging from 3 to 14 m (n = 718 nests). 35% of the nests touched each other. Approximately 60% of the nests were no more than0.5 m from each other. 89% of the nests were located under the roof and the remaining 11% in the corner of a window or under a bal cony.
Keywords: Ornitologija; Lastovke; Kozjansko; bird; ptice; gnezdenje; Kozjanski park